Fine‐needle aspiration in desmoplastic small round cell tumor: A report of 10 new tumors in 8 patients with clinicopathological and molecular correlations with review of the literature. Issue 5 (17th March 2014) - Klijanienko, Jerzy; Colin, Pierre; Couturier, Jérôme; Lagacé, Réal; Fréneaux, Paul; Pierron, Gaëlle; Laé, Marick; Klijanienko, Alice; Brisse, Hervé; Orbach, Daniel; Theocharis, Stamatios
<x xml:space="preserve">Abstract</x> BACKGROUND Desmoplastic small round cell tumor (DSRCT) is a rare round cell sarcoma entity characterized by a specific t(11;22)(p13;q12) translocation, usually intra‐abdominal localization and an aggressive clinical outcome. To date, only 35 DSRCT cases diagnosed by fine‐needle aspiration have been described. METHODS This study reports the cytological diagnosis of DSRCT. Ten tumors from 8 patients were sampled for diagnosis and analyzed to search the characteristic translocation using fluorescence in situ hybridization or reverse transcription polymerase chain reaction methods. RESULTS Smears were always hypercellular and consisted of nonspecific round cell sarcoma. Nuclei were polymorphic round, kidney‐, or heart‐shaped. Nuclear molding was usually present. Paranuclear cytoplasmic densities were obvious and noted in 7 cases. Cytonuclear atypia, mitotic figures, numerous crushed nuclei, and apoptosis were frequently seen. Purple‐stained stroma was present in 8 cases (ranging from few connective tissue fragments to large hyalinized deposits). Molecular studies based on cytological aspirates were performed in 8 patients. The presence of the fusion gene EWSR1‐WT 1 transcript was identified in all, which confirmed the diagnosis of DSRCT. CONCLUSIONS Smears showing poorly differentiated round cells associated with cytoplasmic densities and connective stoma, in a specific clinical context, young adult age, intra‐abdominal localization, suggestive immunocytochemical profile, and a unique cytogenetic abnormality are highly specific and allow an accurate diagnosis of DSRCT. Cancer (Cancer Cytopathol) 2014;122:386–393. © 2014 American Cancer Society.